Functional trait recovery through backcross breeding in blister rust–resistant hybrid white pines (Pinus strobus × Pinus wallichiana) - Benomar, Lahcen; Elferjani, Raed; Lu, Pengxin (Frontiers in Forests and Global Change, 2025)
IntroductionWhite pine blister rust (WPBR) disease, caused by an invasive fungal pathogen (Cronartium ribicola J.C. Fisch), has long been the primary biotic threat to eastern white pine in Canada. A hybridization program initiated in Ontario, Canada in the 1950s aimed to transfer blister rust resistance from Himalayan blue pine to eastern white pine, resulting in WPBR-resistant interspecific hybrids. Metabolic adjustments related to disease resistance may cause trade-offs with tolerance to abiotic stress (e.g., frost, heat, drought). To evaluate the adaptive potential of WPBR-resistant hybrids, it is crucial to understand how morphological and physiological traits change during multi-generation backcrossing, as these shifts may influence both growth performance and resilience to climate change.MethodsWe assessed changes in photosynthetic-related traits, as well as needle morphology and resistance to xylem cavitation of eastern white pine and Himalayan blue pine, and their hybrids with varying levels of white pine parentage ranging from 50 to 87.5%.Results and discussionNeedle length and specific leaf area (SLA) decreased linearly by increasing eastern white pine parentage; inversely, needle density increased by increasing eastern white pine parentage. Variations in needle morphology were not translated into variations in light-saturated photosynthesis (Amax), mesophyll conductance (gm), maximum rate of carboxylation (Vcmax), and maximum rate of electron transport (Jmax). Photosynthetic nitrogen use efficiency (PNUE) decreased, while water use efficiency (WUEi) increased with increasing eastern white pine parentage. Increasing needle density and declining PNUE reflect greater investment in structural tissue, which is commonly associated with frost and drought tolerance. Also, Himalayan blue pine and hybrids were more resistant to xylem cavitation than eastern white pine. Hybrid pines recovered most of their eastern white pine morpho-physiological characteristics after two rounds of backcrossing. Consequently, WPBR-resistant interspecific hybrids should have integrated stress tolerance traits of eastern white pine enabling them to adapt to abiotic and biotic stresses in Canadian boreal forests.